An Analysis of the Cooperative Movement in Brazil in the Light of Regional Development - Ilecki Forgiarini, Deivid; Neumann Alves, Cinara; de Souza Garcia, Alexandre (Cooperativismo & Desarrollo, 2025)
This article explores the cooperative movement in Brazil, identifying a theoretical gap in the understanding of its integration into broader socio-economic frameworks. It aims to assess the movement's role in regional development and autonomy through historical analysis and contemporary evaluation. Utilizing a historical and analytical methodology, the study examines the evolution of cooperatives, their impact on regional development, and challenges faced. Results indicate significant contributions to regional development yet highlight the need for deeper cooperative education and participatory democracy. The conclusion suggests that while cooperatives have fostered regional autonomy and development, greater integration of cooperative principles is essential for sustained and sustainable impact.
Keywords: regional development; Brazilian cooperative movement; cooperatives